Perioperative temperature management in adult anesthesia - Dewa Ayu Karunia Dewi; Eva Dharma Yanti; Adinda Putra Pradhana (Neurologico Spinale Medico Chirurgico, 2019)
Body temperature management is very important to be controlled in surgery because there are so many effects that can be caused due to uncontrolled body temperature during operations such as decreased heart rate, breathing frequency and blood pressure, the skin becomes cyanotic, and even can cause disturbance of consciousness. The body already has a mechanism that can reduce the risk of a decrease in temperature during surgery such as skin vasoconstriction, changes in behavior, shivering and non-shivering thermogenesis. Many factors can influence changes in body temperature thermoregulation in the operating room such as operating room temperature, area of surgery wound, fluid, age, anesthesia, and the duration of the operation, so that we need to know perioperative temperature management.